(untitled) (Proceedings of International Conference on Special Education, 2019)
Pelan Tindakan Orang Kurang Upaya 2016-2022 outlines the strategy to empower people with disabilities and increase their participation in entrepreneurship. Lack of resources to support this mission causes Selayang Community College and Pusat GENIUS@Kurnia to open a training platform for students with special needs to do business. Thus this study has identifies the impact of entrepreneurial training platform and their intention to venture into business. Students with at least six months of experience in Inspired Kitchen and Ausome Cafe have been interviewed using a set of interview protocols. Interview data is analyzed according to the theme. The frequency of themes has been grouped in terms of managing skills and intention to become entrepreneurs. The findings shows that the participants clearly shows the characteristics of entrepreneurs in terms of information seeking, problem solving and persuasion. All participants have a strong intention to do business after graduate. This study provides guidance on the establishment of an entrepreneurial training platform for students with special needs especially in higher institutions.